2016
DOI: 10.1007/s00204-016-1802-z
|View full text |Cite
|
Sign up to set email alerts
|

WHO/UNEP global surveys of PCDDs, PCDFs, PCBs and DDTs in human milk and benefit–risk evaluation of breastfeeding

Abstract: Since 1987, the World Health Organization (WHO) carried out global surveys on polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and polychlorinated biphenyls (PCBs) in human milk. This study presents a review of the three most recent surveys from 2000 to 2010, including DDT. The objective was to identify global quantitative differences and provide baseline information for 52 countries or provide time-trends for countries with previous data. Individual human milk samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(111 citation statements)
references
References 53 publications
4
104
2
1
Order By: Relevance
“…In other words, source proximity and long-range transport need to be taken into account in addition to dietary habits when comparing the exposure of different human sub-populations to persistent organic pollutants. A worldwide survey of concentrations in human breast milk [23] identifies exclusively central and Eastern European countries as having elevated PCB concentrations, consistent with the intensity of PCB emissions in this region (figure 1). Concentrations in breast milk in countries in tropical latitudes and the Southern hemispheric are generally much lower, again reflective of the global distribution of historical PCB emissions.…”
Section: Resultssupporting
confidence: 64%
“…In other words, source proximity and long-range transport need to be taken into account in addition to dietary habits when comparing the exposure of different human sub-populations to persistent organic pollutants. A worldwide survey of concentrations in human breast milk [23] identifies exclusively central and Eastern European countries as having elevated PCB concentrations, consistent with the intensity of PCB emissions in this region (figure 1). Concentrations in breast milk in countries in tropical latitudes and the Southern hemispheric are generally much lower, again reflective of the global distribution of historical PCB emissions.…”
Section: Resultssupporting
confidence: 64%
“…This is explained by excretion of OCs in the breast milk, resulting in lower maternal serum levels of OCs and exposure to breastfeeding children [51]. A recent review concluded that the benefits of breastfeeding far outweigh the potential disadvantages, but argues to plea for further global source-directed methods to reduce human exposure to OCs [52]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, other environmental contaminants frequently measured and detected in breast milk include dioxins, polychlorinated biphenyls (PCBs) and perfluoroalkyl substances (PFAS). Their concentration in European breast milk was reported up to 376 ng/L and 114 ng/kg for perfluorootanoic acid (PFOS) and WHO toxicity equivalent levels for dioxin-like compounds, respectively (Anderson et al 2019;Antignac et al 2016;Cariou et al 2015;van den Berg et al 2017). In contrast to these reports, our experiment highlights the low abundance of mycotoxins in breast milk.…”
Section: Inter-individual Mycotoxin Exposure On Five Consecutive Daysmentioning
confidence: 99%